2013
DOI: 10.4161/trns.24885
|View full text |Cite
|
Sign up to set email alerts
|

Decoding human gene expression signatures in the brain

Abstract: T he evolution of higher cognitive functions in humans is thought to be due, at least in part, to the molecular evolution of gene expression patterns specific to the human brain. In this article, we explore recent and past findings using comparative genomics in human and non-human primate brain to identify these novel human patterns. We suggest additional directions and lines of experimentation that should be taken to improve our understanding of these changes on the human lineage. Finally, we attempt to put i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Seminal work in neuroimaging over the last decade has revealed that human brain activity can be defined by its network properties (Buckner and Krienen, 2013; Goni et al, 2014; Power et al, 2011; Sporns, 2013). Differences in gene regulation and expression have also been related to brain function in many species (Barchuk et al, 2007; Chandrasekaran et al, 2011; O’Connell and Hofmann, 2011) and to the evolution of human higher cognitive functions (Geschwind and Rakic, 2013; Konopka et al, 2012; Wang and Konopka, 2013). Here, we link these diverse levels of analysis by asking whether gene expression in human neocortex is correlated to a property of human functional networks defined by fMRI (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Seminal work in neuroimaging over the last decade has revealed that human brain activity can be defined by its network properties (Buckner and Krienen, 2013; Goni et al, 2014; Power et al, 2011; Sporns, 2013). Differences in gene regulation and expression have also been related to brain function in many species (Barchuk et al, 2007; Chandrasekaran et al, 2011; O’Connell and Hofmann, 2011) and to the evolution of human higher cognitive functions (Geschwind and Rakic, 2013; Konopka et al, 2012; Wang and Konopka, 2013). Here, we link these diverse levels of analysis by asking whether gene expression in human neocortex is correlated to a property of human functional networks defined by fMRI (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Brain development is a highly complex, dynamic, and multistage process that involves precisely sequential cellular and molecular events based on the coordinated expression of many genes (Silbereis et al, 2016;Wang and Konopka, 2013). A major challenge is identifying core genes during each of these events.…”
Section: Discussionmentioning
confidence: 99%
“…Brain development is a multistage process, accompanied by coordinated expression of many genes (G.-Z. Wang and Konopka, 2013). Thanks to availability of spatiotemporal transcriptome of the human brain by BrainSpan (www.brainspan.org); in this study, we investigated to find biological processes as well as signaling pathways, correspondingly involved in the development of PFC of human brain.…”
Section: Discussionmentioning
confidence: 99%